If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -9 = 6y + -1 Reorder the terms: -9 + 5y = 6y + -1 Reorder the terms: -9 + 5y = -1 + 6y Solving -9 + 5y = -1 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -9 + 5y + -6y = -1 + 6y + -6y Combine like terms: 5y + -6y = -1y -9 + -1y = -1 + 6y + -6y Combine like terms: 6y + -6y = 0 -9 + -1y = -1 + 0 -9 + -1y = -1 Add '9' to each side of the equation. -9 + 9 + -1y = -1 + 9 Combine like terms: -9 + 9 = 0 0 + -1y = -1 + 9 -1y = -1 + 9 Combine like terms: -1 + 9 = 8 -1y = 8 Divide each side by '-1'. y = -8 Simplifying y = -8
| T/10=3/35 | | A=Ao/2n | | 3/4=w/18 | | 3(2x-5y)-2(x-3y)= | | 2(3+x)=19 | | -9(y-1)=-8y-6 | | 3/4=w/35 | | -7(-2y+4)-y=4(y-3)-1 | | y=0.95x+6 | | 22-13x=-8-2x-18x | | sen(x)+2cos(x)=1 | | 6x-8=5x+90 | | 3x-40=x-18 | | 5p-3p-30=-18 | | 4x+4=31-5x | | 8x-9+x=180 | | 2x-5+x=2 | | 3x+4=84-5x | | 3x+84=10x+14 | | 2x+17=45-2x | | =5.6e | | 6mn(m+1)= | | =5.6e+8 | | 4x+13=48-3x | | -7(2x-8)+2x=6(x+8) | | 4x+50=2x+90 | | 2x+17=89-6x | | 4(w-1)=6w+1-2(-6w-1) | | 8x+8=x+1 | | 2x(x-5)-(x-3)(x+2)=28-3(3x-1)(3x+2) | | t/27=-4 | | 2.5/y=5/12 |